رقمنة الأملاك العقارية - دراسة حالة الجزائر - طويل، حدة; رحال، إيمان; سلطان، مونية (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الورقة إلى التطرق إلى أحد المواضيع الهامة على الساحة الإدارية والاقتصادية والقانونية للجزائر ألا وهو موضوع الرقمنة، وبالتحديد رقمنة الأملاك العقارية التي تعد العمود الفقري للاقتصاد الوطني وقائد مقطورة التنمية الاقتصادية. لذا أولت له الحكومة الجزائرية أهمية بالغة من أجل رقمنته، كون الرقمنة تسهم في ممارسة الرقابة والإشراف العمراني، كما تعمل على حماية الأملاك العقارية من الاستغلال غير العقلاني. Abstract: This paper aims to address one of the important topics in the administrative, economic and legal arena of Algeria, namely the topic of digitization, specifically the digitization of real estate, which is the backbone of the national economy and the leader of the economic development train. Therefore, the Algerian government has given great importance to its digitization, as digitization contributes to the exercise of urban control and supervision, and works to protect real estate from irrational exploitation.
مداخلة
Keywords: القطاع العقاري; الرقمنة; المحافظة العقارية; البوابة الجغرافية فضاء الجزائر; Real estate sector; digitization; real estate conservation; geographical portal; Algerian space